Profil Tingkat Kesulitan Guru Matematika Dalam Penerapan Pembelajaran Berbasis HOTS Ditinjau Dari Dimensi Perencanaan - Fatma Fela; Edy Nurfalah (IAI Muhammadiyah Sinjai, 2022)
Learning is an evaluation or assessment process that is useful to support improvements in learning, in the assessment it is necessary to have instruments that support students to have creative thinking skills and high-level thinking. This study aims to determine the level of difficulty of mathematics teachers at Madrasah Aliyah in Tuban Regency in implementing Higher Order Thinking Skills (HOTS) based learning in the assessment dimension. The problem of teacher difficulties in the HOTS learning assessment dimension requires the ability of teachers to assess learning outcomes, assess the learning process, and process values ​​in the form of percentage values. This quantitative descriptive study has a population of mathematics teachers who only teach at the Madrasah Aliyah level in the Tuban Regency. This research was conducted using a questionnaire survey method through the Zoho Form application by distributing a questionnaire link. The results showed that the difficulty level of mathematics teachers at Madrasah Aliyah in Tuban Regency towards the application of Higher Order Thinking Skills (HOTS) seen from the dimensions of the assessment in the